Better governance will lead to better taxonomy: response to Raposo et al. (2017) - Garnett, Stephen T.; Christidis, Les (Zootaxa, 2018)
We welcome the recent paper by Raposo et al. (2017) debating our Nature Comment on inadequacies in taxonomic governance and the impact this has on conservation and society (Garnett & Christidis 2017), as well as the opportunity to clarify our views. We admit to surprise at meanings read into our paper by Raposo et al. (2017) that we never intended and that we had not thought were there. As we have also made clear in a separate discussion of our paper (Garnett & Christidis 2018 in response to Thomson et al. 2018), we wish to make clear at the start: (i) that we have no wish to stifle taxonomic research, only to strengthen the legitimacy of its findings; and (ii) we believe that taxonomic research should not consider the consequences for conservation, or society, in its conclusions once transparent taxonomic criteria have been established (Garnett & Christidis 2007), but that taxonomists have an obligation to improve their governance to ensure taxonomic conclusions are of the highest standard.